Bicyclic cyclopentenones via the combination of an iridium-catalyzed allylic substitution with a diastereoselective intramolecular Pauson-Khand reaction - Farwick, Andreas; Engelhart, Jens U.; Tverskoy, Olena; Welter, Carolin; Umlauf, Quendolin A.; Rominger, Frank; Kerr, William J.; Helmchen, Günter (Advanced synthesis & catalysis, 2011)
Enantioselective syntheses of bicyclic cyclopentenones are described. Key steps are an iridium-catalyzed allylic substitution and an intramolecular diastereoselective Pauson-Khand reaction. The diastereoselectivity of the Pauson-Khand reaction was found to be crucially dependent on the unit connecting the propargylic and the olefinic parts of the precursor. Very high degrees of diastereoselection were obtained with an NBoc unit as connector. This methodology has been illustrated by application within an enantioselective formal total synthesis of (−)-α-kainic acid.